Seven-Year Clinical Surveillance Program Demonstrates Consistent MARD Accuracy Performance of a Blood Glucose Test Strip. (September 2018) - Setford, Steven; Grady, Mike; Mackintosh, Stephen; Donald, Robert; Levy, Brian
Background: MARD (mean absolute relative difference) is increasingly used to describe performance of glucose monitoring systems, providing a single-value quantitative measure of accuracy and allowing comparisons between different monitoring systems. This study reports MARDs for the OneTouch Verio® glucose meter clinical data set of 80 258 data points (671 individual batches) gathered as part of a 7.5-year self-surveillance program Methods: Test strips were routinely sampled from randomly selected manufacturer's production batches and sent to one of 3 clinic sites for clinical accuracy assessment using fresh capillary blood from patients with diabetes, using both the meter system and standard laboratory reference instrument. Results: Evaluation of the distribution of strip batch MARD yielded a mean value of 5.05% (range: 3.68-6.43% at ±1.96 standard deviations from mean). The overall MARD for all clinic data points (N = 80 258) was also 5.05%, while a mean bias of 1.28 was recorded. MARD by glucose level was found to be consistent, yielding a maximum value of 4.81% at higher glucose (≥100 mg/dL) and a mean absolute difference (MAD) of 5.60 mg/dL at low glucose (<100 mg/dL). MARD by year of manufacture varied from 4.67-5.42% indicating consistent accuracy performance over the surveillance period. Conclusions: This 7.5-year surveillance program showed that this meter system exhibits consistently low MARD by batch, glucose level and year, indicating close agreement with established reference methods whilste exhibiting lower MARD values than continuous glucose monitoring (CGM) systems and providing users with confidence in the performance when transitioning to each new strip batch.